Quantitative susceptibility mapping in the abdomen as an imaging biomarker of hepatic iron overload. Issue 3 (8th September 2014) - Sharma, Samir D.; Hernando, Diego; Horng, Debra E.; Reeder, Scott B.
<x xml:space="preserve">Abstract</x> Purpose: The purpose of this work was to develop and demonstrate feasibility and initial clinical validation of quantitative susceptibility mapping (QSM) in the abdomen as an imaging biomarker of hepatic iron overload. Theory and Methods: In general, QSM is faced with the challenges of background field removal and dipole inversion. Respiratory motion, the presence of fat, and severe iron overload further complicate QSM in the abdomen. We propose a technique for QSM in the abdomen that addresses these challenges. Data were acquired from 10 subjects without hepatic iron overload and 33 subjects with known or suspected iron overload. The proposed technique was used to estimate the susceptibility map in the abdomen, from which hepatic iron overload was measured. As a reference, spin‐echo data were acquired for R2‐based LIC estimation. Liver R2* was measured for correlation with liver susceptibility estimates. Results: Correlation between susceptibility and R2‐based LIC estimation was R2 = 0.76 at 1.5 Tesla (T) and R2 = 0.83 at 3T. Furthermore, high correlation between liver susceptibility and liver R2* (R2 = 0.94 at 1.5T; R2 = 0.93 at 3T) was observed. Conclusion: We have developed and demonstrated initial validation of QSM in the abdomen as an imaging biomarker of hepatic iron overload. Magn Reson Med 74:673–683, 2015. © 2014 Wiley Periodicals, Inc.